Intention To Avoid Tax Evasion: Religiosity And Understanding Of Tri Pantangan Tamansiswa - Erawati, Teguh; Putri, Fuadhillah Kirana; Kusuma, Amalia Lintang Ayu Nur (Fakultas Ekonomi Universitas Negeri Manado, 2025)
Tax is one of the main sources of revenue for the state to finance government activities. Tax evasion is still a problem that has an impact on depleting the potential for state revenue. This study aims to examine religiosity and understanding of the Tri Pantangan effect on intention to avoid tax evasion. This study uses primary data obtained through a questionnaire with data measurement used Likert scale obtained through google form. A total of 84 samples from accounting students, Sarjanawiyata Tamansiswa University were obtained using the conveniance sampling method. The research findings show that religiosity has a negative effect on intention to avoid tax evasion and understanding Tri Pantangan has no effect on intention to avoid tax evasion. The findings are expected to provide practical contributions that tax authorities can use to design compliance campaigns that integrate religious values to raise public awareness about the importance of paying taxes honestly.